Handbook of Halophytes 2020
DOI: 10.1007/978-3-030-17854-3_87-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic Utilization of Salt-Affected Wasteland for Plant Production

Abstract: The present world population is over 7.7 billion and is growing by the minute. The need to fulfill demands for food, animal fodder, and industrial raw materials is one of the biggest challenges of this century, as is the increase in global pollution. As limited land and water resources are available, strategies are required to use these resources very carefully. More than 1 billion hectares of land worldwide are salt affected and barren. These lands are poor in fertility and unfit for conventional agricultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…S. bigelovii forage effects positively the growth of goat kids and milk production. El-Shaer, [26] reported that sheep lost 26 g day −1 in spring season as compared to summer season (134 g day −1 ). Although pasture reached its best condition, ruminants were incapable of keeping their weights.…”
Section: Animal Meat Quality and Halophytic Foddermentioning
confidence: 99%
“…S. bigelovii forage effects positively the growth of goat kids and milk production. El-Shaer, [26] reported that sheep lost 26 g day −1 in spring season as compared to summer season (134 g day −1 ). Although pasture reached its best condition, ruminants were incapable of keeping their weights.…”
Section: Animal Meat Quality and Halophytic Foddermentioning
confidence: 99%
“…Using plants has particular potential especially in areas where large populations of diverse halophytic species already grow and can be cultivated using saline water for irrigation without using existing arable lands or clearing forests to open new lands (Xu et al, 2020b). By providing a cover on barren lands, halophytes can reduce soil erosion and reduce greenhouse gases by Csequestration; some halophytes are potential sources of oil seeds (Abideen et al, 2015b); others have value in medicines and various other purposes (see Figure 4) (Abideen et al, 2012;Abideen et al, 2014b;Yasin Ashraf et al, 2020). Many perennial halophytic grasses produce enough lignocellulosic biomass under saline conditions to warrant conversion into biofuel (Munir et al, 2021).…”
Section: Biofuel Production From Halophytesmentioning
confidence: 99%
“…Salinity is the most common abiotic stress in arid and semi-arid areas of the world [ 1 ]. Across the globe, 800 million hectares of land are saline [ 2 , 3 ], while in Pakistan, almost 6.8 million hectares are negatively affected by salts [ 4 ]. Salinity adversely affects the morpho-physiological attributes of plants, consequently reducing their yield [ 5 ].…”
Section: Introductionmentioning
confidence: 99%